Efficacy and safety of Latilactobacillus curvatus LB-P9 on hair health: a randomized, double-blind, placebo-controlled clinical trial - Choi, Sun Young; Ko, Eun Jung; Seok, Joon; Han, Hye Sung; Yoo, Kwang Ho; Song, MiKyung; Song, Kyoungsub; Kim, Beom Joon (Frontiers in Nutrition, 2024)
Introduction: Numerous factors influence hair health, including genetic predisposition, hormonal changes, stress, nutritional deficiencies, medical conditions, or medications. With the rising interest in maintaining hair health, alternative approaches such as functional cosmetics and food products are gaining attention. Probiotics, health-beneficial live microorganisms, are emerging as potential candidates for improving hair health. Therefore, this study aimed to evaluate the effects and safety of oral intake of Latilactobacillus curvatus LB-P9 on hair health.The study was a randomized, double-blind, placebo-controlled clinical trial involving participants (aged 18-60 years old) with mild to moderate hair damage. Participants were randomly assigned to the test (receiving LB-P9 supplements) or control (receiving a placebo) groups, respectively. Efficacy was assessed using measures such as hair luster, elasticity, and participant satisfaction. Safety evaluations comprised physical examinations, vital sign measurements, laboratory tests, and observation of adverse reactions.Results: Overall, 80 participants were enrolled in the trial. Significant improvements were observed in hair luster, elasticity, and participant satisfaction in the test group compared to the control group. In the test group, the hair luster parameter increased by 1.65±2.30 (LBNT) at 24 weeks (p<0.001), indicating a 19% improvement over the control group. Subgroup analysis revealed significant improvement in hair luster among females with short hair. Additionally, hair tensile strength, reflecting hair elasticity and participant satisfaction are increased by 10.27±16.40 (gf/mm 2 ) at 24 weeks (p=0.001) in the test group.The subjective indicator of participant satisfaction, which improves as survey scores decrease, significantly decreased in the test group by -17.81±14.35 points (p<0.001) after 24 weeks of consuming the test food than before consuming it. No significant adverse reactions were reported, and safety evaluations indicated no adverse effects linked to LB-P9 consumption.Probiotics, including LB-P9, may serve as an alternative in the management of hair health.The findings of this study support the possible benefits of LB-P9 supplementation in enhancing hair luster and elasticity.